Teacher leadership: an investigation of early-career teacher leadership development of public schools in Northwest China, Gansu Province - Li, Lin (2022)
The strong advocacy and the quest for teacher leadership in the twenty-first century bear the premise that teacher leadership is an important ingredient in teacher professional development, student performance, and school effectiveness (Bush, 2016; Katzenmeyer and Moller, 2009; Wang and Ho, 2019). There is a paucity of the investigation of teacher leadership of young and early-career teachers, especially in Asian context where educational systems are highly centralised (Bush and Ng, 2019; Szeto, 2020). This study is to investigate teacher leadership development of early-career teachers in general and specifically on factors that facilitate as well as factors that impede teacher leadership development in public schools of Northwest China, Gansu Province. This study was underpinned by the constructivist theory (Lambert, 1998; 2003), distributed leadership theory (Muijs and Harris, 2006), and the social cognitive theory (Bandura, 1997) through an ecological lens (Bronfenbrenner, 2005).